The genomic and phenotypic diversity of Schizosaccharomyces pombe - Jeffares, Daniel C; Rallis, Charalampos; Rieux, Adrien; Speed, Doug; Převorovský, Martin; Mourier, Tobias; Marsellach, Francesc X; Iqbal, Zamin; Lau, Winston; Cheng, Tammy M K; Pracana, Rodrigo; Mülleder, Michael; et al. (Nature genetics, 2015)
Natural variation within species reveals aspects of genome evolution and function. The fission yeast Schizosaccharomyces pombe is an important model for eukaryotic biology, but researchers typically use one standard laboratory strain. To extend the usefulness of this model, we surveyed the genomic and phenotypic variation in 161 natural isolates. We sequenced the genomes of all strains, finding moderate genetic diversity (π = 3 × 10(-3) substitutions/site) and weak global population structure. We estimate that dispersal of S. pombe began during human antiquity (∼340 BCE), and ancestors of these strains reached the Americas at ∼1623 CE. We quantified 74 traits, finding substantial heritable phenotypic diversity. We conducted 223 genome-wide association studies, with 89 traits showing at least one association. The most significant variant for each trait explained 22% of the phenotypic variance on average, with indels having larger effects than SNPs. This analysis represents a rich resource to examine genotype-phenotype relationships in a tractable model.
Keywords: Genetic Variation; Phenotype; genetická variace; celogenomová asociační studie; Genome-Wide Association Study; genotyp; jednonukleotidový polymorfismus; Genomics; fenotyp; genomika; Schizosaccharomyces; Genome, Fungal; Humans; genom fungální; lidé; Genotype; Polymorphism, Single Nucleotide